2013
DOI: 10.2190/om.67.1-2.f
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Additional Support Services on Caregivers of Hospice Patients and Hospice Social Workers

Abstract: Family caregivers often suffer higher levels of physical and emotional distress when caring for a chronically or terminally ill family member. Providing this kind of care to a loved one at the end of life contributes to increased stress, health problems, and a decreased quality of life. The Hospice Caregiver Support Project provided support services to caregivers identified by the hospice social worker as needing this support and/or assistance. Results from the project show that offering additional services re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Hospice care usually encompasses a broad range of services that includes palliative care, emotional support, and spiritual resources for terminally ill patients and their families. The provision of tangible and emotional support services to caregivers of hospice patients, typically family members of the patient, has been related to better psychological well-being for caregivers (Empeño et al, 2013; Teno et al, 2004). Despite the need to improve access to high-quality end-of-life services among underserved populations, research shows marked disparities in hospice care utilization among Hispanics (Cohen, 2008; Kreling et al, 2010; Colon, 2012; Taxis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hospice care usually encompasses a broad range of services that includes palliative care, emotional support, and spiritual resources for terminally ill patients and their families. The provision of tangible and emotional support services to caregivers of hospice patients, typically family members of the patient, has been related to better psychological well-being for caregivers (Empeño et al, 2013; Teno et al, 2004). Despite the need to improve access to high-quality end-of-life services among underserved populations, research shows marked disparities in hospice care utilization among Hispanics (Cohen, 2008; Kreling et al, 2010; Colon, 2012; Taxis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During this time, family members experience increased stress levels and physical ailments, demonstrating how they have unmet needs (Barazzetti et al, 2010; Empeno, 2013; Tsigaroppoulos et al, 2009). Collectively, studies have confirmed that providing sufficient information is critical to meeting informal caregivers' needs and assisting families through this stressful time.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, studies have confirmed that providing sufficient information is critical to meeting informal caregivers' needs and assisting families through this stressful time. Recent research concluded that group education was an effective way of supporting informal caregivers (Applebaum & Breitbart, 2013;Hudson & Aranda, 2013;Hudson et al, 2005;2013). Further, a Cochrane report noted that providing community care services, including caregiver education, was beneficial in allowing patients to die at home, if that was their choice (Gomes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%